2022
DOI: 10.3151/jact.20.254
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Deep-Sea Monitoring of Cement Mortar Specimen at a Depth of 3515 m and Changes in Mechanical Properties after Exposure to Deep Sea Condition

Abstract: The results of the first-ever in-situ monitoring of a large mortar specimen at a depth of 3515 m in the Nankai Trough are presented in this study targeted at creating a technology platform for in-situ monitoring and evaluation of cement-based materials at the seabed to realize deep-sea infrastructures. We successfully monitored in situ the development of strain and hydraulic pressure in the specimen. In addition, the short-term behavior of the specimen can be explained by hydraulic confinement and stress relax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…In a real deep-sea field, PC mortar specimens were severely disintegrated only after 1.5 years exposure [1]. As there could be a size effect on seawater attack, a large size specimen was also exposed [2,9]. Figure 1 shows 350 Φ mm × 400 mm-sized PC mortar specimen (water to cement ratio = 0.6, which was the same with [1]) exposed on the deep seafloor with a depth of 3515 m for 309 days.…”
Section: Portland Cement-based Materialsmentioning
confidence: 95%
See 3 more Smart Citations
“…In a real deep-sea field, PC mortar specimens were severely disintegrated only after 1.5 years exposure [1]. As there could be a size effect on seawater attack, a large size specimen was also exposed [2,9]. Figure 1 shows 350 Φ mm × 400 mm-sized PC mortar specimen (water to cement ratio = 0.6, which was the same with [1]) exposed on the deep seafloor with a depth of 3515 m for 309 days.…”
Section: Portland Cement-based Materialsmentioning
confidence: 95%
“…Decalcification of C-S-H, formation of thaumasite and M-S-H may occur at the surface as reported in [1,11], and these could cause disintegration of the specimen. Lots of pinhole-like popouts [5], where brucite, calcite and ettringite were detected in Fig. 2, were observed at the surface.…”
Section: Portland Cement-based Materialsmentioning
confidence: 95%
See 2 more Smart Citations
“…Wang et al reported that water penetration during pressurization may cause microstructural damage to concrete [23]. Following 309 days of exposure at a depth of 3515 m, a specimen's compressive strength decreased by 27.7%, as assessed by Takahashi et al [24]. These investigations primarily focused on the impact of low temperature and hydraulic pressure on the mechanical characteristics and microstructure of cement-based materials.…”
Section: Introductionmentioning
confidence: 99%